DIAGNOSTIC SPECIFICS OF PULMONARY VENO-OCCLUSIVE DISEASE - E. A. Zhuk; N. V. Kirichenko; S. E. Myasoedova; T. A. Pobedinskaya; V. P. Vasilyeva (Российский кардиологический журнал, 2012)
The authors present the two-year follow-up of a female patient with severe pulmonary hypertension and a rare pathology – pulmonary veno-occlusive disease. Due to the treatment with low-dose prednisolone, in combination with warfarin, coraxan, and oxygen, the clinical status of the patient remains stable.